Cross-Cultural Design 6th International Conference, CCD 2014, Held as Part of HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014, Proceedings - Rau, P.L.Patrick (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
This volume constitutes the refereed proceedings of the 6th International Conference on Cross-Cultural Design, CCD 2014, held as part of the 16th International Conference on Human-Computer Interaction, HCI International 2014, held in Heraklion, Crete, Greece, jointly with 13 other thematically similar conferences. The total of 1476 papers and 220 posters presented at the HCII 2014 conferences was carefully reviewed and selected from numerous submissions. The papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. They thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The 76 papers included in this volume deal with the following topics: cross-cultural product and service design; cross-cultural issues in interaction; social aspects and implications of cross-cultural design; cross-cultural issues in e-commerce, marketing and branding; cross-cultural design for knowledge sharing and learning; cross-cultural design for the smart city and cross-cultural design for creativity.